2019
DOI: 10.9734/ajaees/2019/v37i430275
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Outcomes of Krishi Vigyan Kendra, Central Research Institute for Dryland Agriculture Technologies by Farmers in South India

Abstract: Rainfed areas are subjected to climate change through extreme weather events, decrease of water availability and decrease in agricultural productivity. The problem to be addressed is the limited access to and exchange of, information and knowledge related to agriculture and food security at local, national, and regional levels. Krishi Vigyan Kendras (KVKs) act as a crucial player in technology assessment, refinement and demonstration. Technology adoption to be successful depends on successful technology assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The primary data required for the study were collected from selected sample respondents through specially prepared schedules included the data relating to the profile of respondents, adoption of various improved agricultural practices. Shankar et al [6] analyzed impact of interventions given by KVK between adopting and non-adopting farmers and found that there is a significant difference in knowledge score of 7 between adopters and non-adopters indicating significant difference in the knowledge gained by adopting farmers over non-adopting farmers [6]. The entire schedule was sent by Agricultural Technology Research Institute (ATARI), Zone -IV to Krishi Vigyan Kendras, Nagaon with an objective to measure the overall evaluation ICAR schemes.…”
Section: Methodsmentioning
confidence: 99%
“…The primary data required for the study were collected from selected sample respondents through specially prepared schedules included the data relating to the profile of respondents, adoption of various improved agricultural practices. Shankar et al [6] analyzed impact of interventions given by KVK between adopting and non-adopting farmers and found that there is a significant difference in knowledge score of 7 between adopters and non-adopters indicating significant difference in the knowledge gained by adopting farmers over non-adopting farmers [6]. The entire schedule was sent by Agricultural Technology Research Institute (ATARI), Zone -IV to Krishi Vigyan Kendras, Nagaon with an objective to measure the overall evaluation ICAR schemes.…”
Section: Methodsmentioning
confidence: 99%
“…It had been measured with the scale developed by the Pareek and Trivedi (1964) and weightages as the no land, less than one acre, 1-5 acre, 5-10 acre, 10-15 acre, 15-20 acre, more than 20 acre. Socio-economic status (rural) and the weightages had been given as No land -(0), less than one acre -(1), 1-5 acre -(2), 5-10 acre -(3), 10-15 acre -( 4), 15-20 acre - (5), more than 20 acre -(6).…”
Section: Size Of Holding(x 4 )mentioning
confidence: 99%
“…Technology adoption to be successful depends on successful technology assessment, refinement and demonstration. Hence, the role of KVKs is of paramount importance in the above processes [5]. Overall adoption quotients for different aspects of agricultural production practices were highly skewed towards beneficiary respondents [6].…”
Section: Introductionmentioning
confidence: 99%